Peran Problem Based Learning terhadap Proses Berpikir Kritis Siswa - Oktavihari, Dita; Primajati, Gilang (Jurnal el-Huda, 2025)
Critical thinking skills are important 21st-century skills that students must have to face global challenges. However, the reality in the field shows that most learning is still teacher-centered and oriented toward memorization, not problem-solving. This article aims to examine the role of the Problem-Based Learning (PBL) model in developing students' critical thinking skills through a literature study approach. The method used is a literature study with a review of 20 scientific articles published in the last five years, using the PRISMA protocol. The results of the analysis show that PBL consistently has a positive impact on improving students' critical thinking skills at various levels and subjects, especially mathematics. The aspects of critical thinking that develop include analysis, evaluation, inference, and explanation. PBL has also been shown to increase students' motivation, activeness, and courage in expressing their opinions. The use of digital media such as e-modules, interactive LKPD, and integration with the flipped classroom and STEM approaches further strengthen the effectiveness of PBL. In addition, individual characteristics of students such as interpersonal intelligence and self-efficacy also influence the success of PBL implementation. These findings strengthen that PBL is a strategic and adaptive learning approach to developing critical thinking skills systematically and sustainably.